Understanding the Role of Nationalism in "New Democracies" - Matić, Davorka (1999)
The transition from communism to democracy has raised numerous discussions regarding the nature of postcommunism in Eastern Europe. According to the author, the two main approaches used to explain the collapse of communism – one that claims that resurrected civil society triumphed over totalitarianism, and, the other that avers Eastern Europe’s propensity for irrationalism and a political behaviour based on ethnic exclusion and hatred – overlook the unique nature of postcommunism. In order to properly grasp the nature of this phenomena, the author argues that one must first understand the intrinsic nature of Eastern Europe’s transformation. To do this requires an analysis of the social structures that drive political change and identifying the social group that is the main bearer of transformation. The author believes that though her analysis focuses primarily on the case of former Yugoslavia, and Croatia in particular, the conclusions she draws from it are also valid for other East European countries: that the nation is regarded as the principal catalyst for political change and that nationalism is the main legitimizing principle of emerging states. This analysis rejects the common view according to which nationalism is casually discounted as an irrational political movement that is fundamentally hostile to democracy and freedom. Quite the contrary. Throughout Eastern Europe nationalism has had a positive role in bringing down communism and creating a space for democracy to take root. Still, tension exists between nationalism and the democracy it spawned. To understand this paradox requires an extensive sociological and historical study of the particular conditions within which a particular community defines the goals of nationalism and the specific content of its main undergirding concepts like nation and state. Identifying the circumstances within which nationalism begins to act as an obstacle to the establishment of full-fledge democracy is key to understanding the political reality of today’s Croatia and of many other East European “new democracies”. Nationalism works differently in different socio-political conditions – differently in countries that recently achieved independence from countries with a long tradition of sovereign statehood, differently in countries with an underdeveloped or non-existent civil society from those with a strong civil society, differently in countries that are economically prosperous from those that are experiencing economic hardship. All these factors, not nationalism per se, determine the overall prospects for liberal democracy in Eastern Europe.
ENG